2011
DOI: 10.1074/jbc.m111.257105
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Protein p63/Nuclear Factor κB Feedback Loop in Regulation of Cell Death

Abstract: Background: TP53 members and NF-B respond to stresses. Results: TAp63␣ induced the expression of RelA and downstream genes involved in cell cycle arrest or apoptosis. TAp63␣ and RELA formed protein complexes resulting in their mutual stabilization, and TAp63␣ induced the RelA transcription. Conclusion:We defined a novel a feedback loop between NF-B and TP63. Significance: TP53 members and NF-B contribute to the regulation of cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 68 publications
0
10
2
Order By: Relevance
“…29 Thus, p63-induced NF-jB can be pro-or anti-apoptotic, depending on the cellular environment. 28 This case series found no statistically significant difference in NF-jB expression between pcDLBCLL and pcFCLL, although there are multiple alternate NF-jB epitopes not assessed in this study. Nevertheless, all NF-jB positive cases coexpressed p63, and this may represent another mechanism for dysregulation of p63 expression.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…29 Thus, p63-induced NF-jB can be pro-or anti-apoptotic, depending on the cellular environment. 28 This case series found no statistically significant difference in NF-jB expression between pcDLBCLL and pcFCLL, although there are multiple alternate NF-jB epitopes not assessed in this study. Nevertheless, all NF-jB positive cases coexpressed p63, and this may represent another mechanism for dysregulation of p63 expression.…”
Section: Discussioncontrasting
confidence: 56%
“…Conversely, a novel anti‐apoptotic pathway in mature B cells has been described in which NF‐κB up‐regulates TAp63 expression that transactivates BCL‐2 gene expression . Thus, p63‐induced NF‐κB can be pro‐ or anti‐apoptotic, depending on the cellular environment . This case series found no statistically significant difference in NF‐κB expression between pcDLBCLL and pcFCLL, although there are multiple alternate NF‐κB epitopes not assessed in this study.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…On the other hand, we show that HHK exposed to pepsin produces higher transcriptional levels of Tp63, compared to their corresponding controls but a trend of decreased transcriptional activity at low pH (Fig 5B-a). These data in HHK are supported by the identified inverse correlation between transcriptional levels of Tp63 and RELA(p65) [51], but a significant positive linear correlation to Tp53 with apoptotic function (Fig 6C, 6D, 6E and 6F) [46,52]. …”
Section: Discussionmentioning
confidence: 63%
“…TAp63 isoforms acted as tumor suppressors by regulating senescence through p53-independent pathways (25), whereas ∆Np63 isoforms enhance proliferation and inhibit apoptosis (26,27). A recent report showed that TAp63 regulates NF-κB transcription and protein stability, subsequently leading to the cell death phenotype (28). Another report showed TAp63 is a transcriptional target of NF-κB, which may play a role in cell proliferation, differentiation and survival upon NF-κB activation (29,30).…”
Section: Discussionmentioning
confidence: 99%